Pharmaceutical Care for Smoking Cessation: A Pilot Study on Understanding Knowledge and Experience Through a Mixed-Methods Approach - Lorensia, Amelia; Pratama, Anggara Martha; Wardani, Mariani Ika; Suryadinata, Rivan Virlando; Raharjo, Dian Natasya; Budipramana, Krisyanti (Jurnal Sains dan Kesehatan, 2024)
Smoking is one of the biggest threats to public health in the world, so pharmacists should have a role in a multidisciplinary team to provide pharmaceutical care in smoking cessation in pharmacy. The research purpose was to determine the level of knowledge and experience of pharmacist pharmacy services on smoking cessation programs at pharmacists in East Surabaya. This research was mixed-method research, using the explanatory sequential design strategy. Data collection was carried out from October 2021 to January 2022 in Surabaya, East Java, Indonesia. The research variable were knowledge and experience related to pharmaceutical care in smoking cessation. The sample were pharmacists who carried out clinical pharmacy services at pharmacies in East Surabaya. Respondents were interviewed in depth until the data reached the saturation level (saturation so that no new answers/explanations are found) in order to obtain good and usable qualitative data. This study involved 40 respondents. Most of the respondents had sufficient knowledge level (57.50%). Many participants attended seminars on smoking cessation (55%), but none of the respondents had experience in pharmaceutical services. Some respondents have experience in giving advice on smoking cessation to patients during drug delivery at pharmacies (62.50%). Most of the respondents knew dangers of smoking and its relation to health, but most of them cannot explain the theoretical mechanism of the disease pathophysiologically. Pharmacists in pharmacies had sufficient knowledge about smoking cessation, but the practice of pharmaceutical services was still lacking. This could be due to the need to improve information regarding smoking cessation regulations for health workers. Keywords:          experience, knowledge, pharmacist, smoking scessation